O conhecimento tático declarativo e a distribuição de jogo do levantador de voleibolL: da formação ao alto nível - Cristino Julio Alves da Silva Matias (2009)
The purpose of this study was to assess the declarative knowledge and tacticaldistribution of the game of volleyball setters, experts, of different ages. Thesample was composed of the setters: male and female, champions of estatesSao Paulo and Minas Gerais, setters of the competitions promoted by federationsin the age: under-14, under-15, under-17, and under-20 and a championprofessional of the Men's and Women's Superleague. The sample consisted of 18setters. The combination of qualitative and quantitative approach was used.Qualitative approach was applied in an individual interview and semi-structuredwith reference to the grid tactical declarative knowledge of setter. (QUEIROGA,2005; QUEIROGA et al., 2005). Quantitative approach was applied in the test ofdeclarative knowledge Tactical Setter (MATIAS, GRECO 2009) and SOS-vgsenabling the analysis of the distribution of the setter match, used in studies ofMoutinho, Marques and Maia (2003) and Ramos et al. (2004). Through the SOSvgswere analyzed eighteen end of this survey, were evaluated in all 67 sets. Thetexts of eighteen semi-structured interviews were coded, compared and groupedby similarity of meaning. Qualitative approach was confirmed in the fourdimensions of tactical grid of declarative knowledge of the survey: PersonalCharacteristics, Virtuosity of the Player, Sources of Knowledge and Indicators forGame Tactical Decision Making. A new category was cited in size of KnowledgeSources: Reading. Indicators in the size of the game for Tactical Decision Makingemerged categories: Number of Spikers Moved, Service Opponent Features,Tactical and Technical Characteristics of our Players to Pass and Dig and Coach.In the quantitative approach, the results of the Test of Knowledge TacticalDeclarative demonstrated the tactical expertise of the surveys, all were able tomake the right decision and justify the decision exactly for this investigation wasapplied the Spearman's correlation tests showed that a significant association,p=0.000, in all ages. By applying the Kruskall-Wallis test and Manny-Whitney therewas a difference of step with the other professional on the tactical knowledge ofspecific declarative setter, both in males and females, as the level of significanceof tests were less than 0.05.Furthermore, the results of the analysis of distributionof game, via SOS-VGS, showed a broad dependence among the conditions forsetting and conditions of completion with the number of attackers involved, thetime of attack and the area of attack for this investigation was applied the FisherExact test and there was a p.0.05. By means of descriptive data has been agreater use of setting in suspension, increased use of fast attack, a distributionbetween the positions of the more balanced and more situations with the creationof block is composed of an opponent or any player. The triangulation of thequalitative approach with quantitative evidence that the setter, even with idealconditions for setting, focuses its activities in certain attackers, for not havingconfidence and tactical and technical limitations of the other players in their finaloffensive actions. Through triangulation was possible to conclude that the settersare constantly changing, regardless of years of practice in volleyball, withreferences to all about the importance of training as a source of knowledge.